1976
DOI: 10.1111/j.1365-2621.1976.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of unmodified and chemically‐modified tapioca starch granules as revealed by the freeze‐etching technique

Abstract: The ultrastructure of tapioca starch granules was studied using the freezeetching technique in an attempt to overcome the problems associated with the other methods of preparation for electron microscopy. A chemicallymodified tapioca starch was also studied to ascertain whether chemical modification affected granule structure. Variations in fracture faces were observed in both modified and unmodified granules suggesting that organization within the granules was not homogenous. Particles were present on granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the control samples starch granules had concentric rings through the entire cross section where the stain had penetrated (Figure 9). Hard bean samples had granules that stained only slightly and irregularly, generally with the most intense staining in the center of the granule, where water appears first during soaking (Allen et al, 1976). It is suggested that as the soft beans have unrestricted cell separation (leading to increased water uptake), more complete in situ swelling of the granules is allowed, making the granule more susceptible to stain penetration.…”
Section: Resultsmentioning
confidence: 99%
“…In the control samples starch granules had concentric rings through the entire cross section where the stain had penetrated (Figure 9). Hard bean samples had granules that stained only slightly and irregularly, generally with the most intense staining in the center of the granule, where water appears first during soaking (Allen et al, 1976). It is suggested that as the soft beans have unrestricted cell separation (leading to increased water uptake), more complete in situ swelling of the granules is allowed, making the granule more susceptible to stain penetration.…”
Section: Resultsmentioning
confidence: 99%